2022
DOI: 10.32920/19082399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Who Still Watches the Olympics Anyway?” An Exploratory Study of Generation Z and Their Digital Olympic Brand Experience

Abstract: Despite being the most watched sporting event in the world, the Olympic Games have struggled to maintain relevancy amongst younger audiences (Pentony, 2016). The purpose of this study was to explore Generation Z’s Olympic brand experience. Using the Theory of Planned Behaviour (TPB) as a theoretical lens, this research employed a focus group methodology to uncover what the Olympic brand means to a sample Generation Z population and gain valuable insight relative to the influence of TPB variables on this genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…The study 24 suggests that the training methodologies used in youth sports could further exacerbate RAE. Additionally, Generation Z's disengagement from the Olympic brand, as identified by Waseem et al 25 , could potentially impact RAE by reducing the pool of young athletes. Studies have shown that teams with a higher number of athletes born earlier in the year tend to perform better in tournaments 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The study 24 suggests that the training methodologies used in youth sports could further exacerbate RAE. Additionally, Generation Z's disengagement from the Olympic brand, as identified by Waseem et al 25 , could potentially impact RAE by reducing the pool of young athletes. Studies have shown that teams with a higher number of athletes born earlier in the year tend to perform better in tournaments 9 .…”
Section: Discussionmentioning
confidence: 99%